Between the popular and the philosophical: micromachisms - Gavilanes Bravo, Susana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The main objective of this article is to analyse parto f the philosophical discourse, as well as that expressed in popular music with respect to women and indirectly to sexual diversity Philosophy and verses contained in the lirics of popular song are relate to discrimination that translates into implicid behaviors recognized as micro –machismos and other explicid ones that would be macro-consequences,such as allstypes of violence wicht afters as spiral culminate in femicides. Tryng to understandthe discursive structure that these acts keep, acquires relevance since the populationreferred to, lives under permanent threat ,for centuries.